THE EFFECT OF BIOSTIMULANTS ON THE FORMATION OF ROOT NODULE BACTERIA IN MUNG BEAN VARIETIES - Kholiqov Mukhridin Bakhromjon ugli (Innovate Conferences, 2025)
This article presents the results of three-year field experiments conducted from 2022 to 2024, studying the dynamics of root nodule formation in “Durdona” and “Marjon” mung bean varieties and the influence of biostimulants on this process. The research demonstrated that the application of biostimulants Fitobiosol, Gumi–20, and Avangard Start significantly enhanced the activity of rhizobacteria and markedly stimulated the formation of root nodules.
Keywords: Biostimulant, Phytobiosol, Gumi–20, Avangard Start, mung bean, Durdona, Marjon, root nodules, rhizobacteria, symbiosis, development, nitrogen fixation, experiment, observation.